The application of accelerometers to measure movements of upper limbs: Pilot study - Kutilek, P.; Volf, P.; Cerny, R.; Hejda, J. (Acta Gymnica, 2017)
Background: Even though inertial measurement units (IMU) are already being used experimentally for evaluating movements of segment of the axial skeleton, no studies have been found which have used IMUs to measure the behavior of the segments of upper limbs during quiet stance.